Improvement of the model of structural-mechanical and thixotropic properties of meat batters - Oshchypok, Ihor; Kushniruk, Halyna; Masliichuk, Olia; Vivcharuk, Olga; Pauk, Oksana (Technology audit and production reserves, 2026)
The object of research is the thixotropy of meat batters with different ingredient compositions characteristic of sausage products. The research analyzes modern approaches to evaluating the rheological properties of meat emulsion systems and summarizes the factors influencing their structural organization. The regularities of changes in viscous-plastic characteristics of pork and turkey batters under different levels of load are investigated, and the features of structural destruction and recovery are established. A comprehensive assessment of thixotropic properties is based on the analysis of the structural-mechanical characteristics of batter systems during their formation with various ingredients. It has been demonstrated that the thixotropic state depends on the concentration of protein components and the degree of hydration of the protein system, which determines the stability of the sausage matrix during mechanical processing. The shear stress was calculated for time intervals in the range of 1–1000 s. The output parameters of the proposed model were adapted to the properties of soft meat batters: for minced pork, coefficients A = 80 Pa and B = –12 were adopted, and for minced turkey, A = 60 Pa and B = –9. Since the value of B is negative for both types of raw materials, this confirms the presence of pronounced thixotropic properties in the studied systems. Controlling these parameters allows regulation of the thixotropy of the batter to achieve optimal consistency and structural stability of the finished product. Thixotropic properties play a crucial role in technological operations, including grinding, mixing, filling casings, and structure formation during thermal processing. Excessive structural stability complicates processing, while excessive thixotropy reduces the shape retention of products. The determination of rheological parameters allows predicting the behavior of batter systems under production conditions, ensuring stable texture and high product quality. The results obtained have practical value for optimizing technological regimes in sausage production and developing new products with predictable rheological properties.